(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2016)
Digital Technology is radically changing the way how business and governments operate in today’s scenario. From how businesses and governments interact with customers, citizens and suppliers, to how they manage their employees; digitization has entered almost every aspect of our lives. The field of HR is also one of the areas where digital technology has found its way. Human resource management is now evolving into a more technology-based profession. Gone are the days when HR function shouldered the responsibility for managing people in their old traditional ways. Transformation of HR through digital technology has become call of the day. In the light of this rapidly changing scenario where digitization is evolving at a breakneck speed; HR departments that choose to ignore this transformation could face obsolescence. This research paper talks about the probable reasons why transformation in the field of HR is required and what will be its impact on the business performance. This is because many organizations may undertake this activity just for the sake of it. It is quite possible that a transformation will make a little impact on the organization. The paper also focuses on the benefits and hindrances of digital technology in the area HR and the future trends that can be seen in this field so that the companies can make the best advantage of this transformation.